1977
DOI: 10.1159/000240938
|View full text |Cite
|
Sign up to set email alerts
|

Functional Autonomic Innervation of Mammalian Cardiac Pacemaker during the Perinatal Period

Abstract: Sinoatrial node pacemaker tissues from perinatal and adult rabbits, guinea pigs and rats were examined in vitro. Changes in spontaneous pacemaker rate produced by stimulation of intranodal vagal and sympathetic nerve endings, were taken as a measure of functional postganglionic innervation of the pacemaker. Results show marked species differences in the development of functional innervation of the cardiac pacemaker in the perinatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Seven-day old rabbits and guinea pigs display adult cholinergic responsiveness to stimulation (Vlk and Vincenzi, 1977). Neonatal rabbits, however, seem to display some functional deficiency of adrenergic innervation as manifested by lack of blood pressure increase and heart rate decrease after asphyxiation.…”
Section: Postnatal Electrophysiology Of the Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven-day old rabbits and guinea pigs display adult cholinergic responsiveness to stimulation (Vlk and Vincenzi, 1977). Neonatal rabbits, however, seem to display some functional deficiency of adrenergic innervation as manifested by lack of blood pressure increase and heart rate decrease after asphyxiation.…”
Section: Postnatal Electrophysiology Of the Heartmentioning
confidence: 99%
“…Histochemical studies suggest that ventricular innervation develops later than that of the atria in the rat (De Champlain et al, 1970). The cholinergic innervation is also structurally and functionally immature at birth in the rat heart (Truex et al, 1955;Winckler, 1969;Vlk and Vincenzi, 1977;Horackova et al, 2000). Neuropeptide Y and tyrosine hydroxylase positive nerve fibers are reported to increase rapidly during the first 2 weeks postnatally and reach adult levels by the third week (Nyquist-Battie et al, 1994).…”
Section: Comparative Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Egbert and Katona (7) have shown in the kitten that, even if heart rate is higher during REM sleep than during quiet (NREM) sleep, there is development of a parasympathetic dominance with age during normal, unchallenged sleep. A possible effect of the maturation of the cardiac pacemaker itself cannot be well addressed from our study as it was cross-sectional and has rarely, if ever, been resolved in animal models (20). However, studies of pharmacologically denervated hearts in kittens or other mammals have shown that the intrinsic rate changes are species dependent and can be associated with an heart rate increase (7, 2 1-23).…”
mentioning
confidence: 95%
“…Moreover, the study of the development of autonomic activity is complicated by interspecies differences in rates of sympathetic and parasympathetic development (21 ), state of maturity of neurohumoral control at the time of birth (22), and the extent of development of the organ system that is innervated (23). Whether the parasympathetic nervous system is mature in the early postnatal period in the dog or in man is controversial ( 13,16,17,(24)(25)(26) .a., superfusion with Jso and Ach 10-1 M; X, superfusion with Iso and Ach 10-…”
Section: Resultsmentioning
confidence: 99%